IMPLEMENTASI STRATEGI PEMASARAN MELALUI WEBSITE SCALECRAFTERS UNTUK PRODUK DIORAMA - Fiska Dewi; Ahmad Nouval Riant; Lukman Abdul Azizul Hakim (CV. Denasya Smart Publisher, 2026)
Limited market reach, promotional capital, and distribution barriers are the main constraints for diorama artisans. This study aims to develop ScaleCrafters, an e-commerce platform designed to enhance product visibility and operational efficiency through digital marketing strategies. The research method includes user needs analysis, web-based system design, and the implementation of integrated digital marketing strategies, including SEO, social media marketing, and User Experience (UX) optimization. This platform facilitates online transactions and product customization between artisans and consumers. The results indicate that ScaleCrafters effectively expands market penetration, reduces marketing costs, and optimizes sales management for the diorama craft industry sustainably.